Optimization of glutinous rice crackers incorporated with green banana (Musa sapientum L.) flour and cricket (Acheta domesticus) powder - Phal, Sengleap; Fuangpaiboon, Nattavong; Hirunsorn, Pimnibha; Tangwongchai, Ratchada (Asia-Pacific Journal of Science and Technology, 2024)
Due to the trend of functional food, essential nutrients were added to various kinds of food to enhance nutritional value. Considering alternative and sustainable sources of those nutrients is a challenging issue in food innovation. In this study, green banana flour (GBF) and cricket powder (CP) were used as sources of dietary fiber and protein, respectively, to improve nutritional quality in glutinous rice crackers. Therefore, this research aims to investigate the effects of formulation on the quality of rice crackers. Mixture design was used to formulate the glutinous rice crackers. The components consist of glutinous rice flour (GRF), GBF, and CP which were set at 50-100, 0-35, and 0-15%, respectively. Response surface methodology was used to optimize the appropriate levels of ingredients and examine the effects on the physical, chemical, and sensory properties of glutinous rice crackers. It was observed that higher GBF and CP contents increased hardness and bulk density which led to a decrease in expansion ratio and overall liking score. The optimum area was discovered by overlaying contour plots for the criteria responses and applying ingredient levels that set up limits of acceptable quality for each factor. The optimal point suggested 78.87% GRF, 16.07% GBF and 5.06% CP which will produce a rice cracker with good textural properties (2.15 expansion ratio, 0.29 g/cm3 bulk density, and 997.70 g maximum force), nutritional value (6.83% protein and 4.10% total dietary fiber), and consumer acceptance (6.14 overall-liking score).